An Increasing Reading Interest and Literacy Development Through the Creation of Pioneer Libraries for PAUD Students - Santi Riana Dewi; Santi Octaviani; Andari; Martina Rahmawati Masitoh (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
At this time the existence of a pioneer library is an important thing that must be improved in quality and quantity for the purposes of scientific development. Especially during the pandemic, school children tend to prefer playing games using gadgets or cellphones rather than reading books. Therefore, it is necessary to increase reading interest and literacy development for school students, including PAUD students. The lack of availability of books and other supports is the main reason for the lack of interest in reading and the development of literacy. Community service begins with conducting interviews with PAUD leaders and identifying the situation in PAUD, then continuing with providing motivation, assistance in improving literacy and donating reading books and other supports in order to form a pioneer library for students. The creation of a library is intended for students with the guidance of teachers and parents of students. Currently there are 4 teachers and 25 students. Before the service at PAUD there was no library with adequate books and supports. After the implementation of the program, teachers and students became increasingly enthusiastic about increasing book reading activities and improving overall literacy. In the future, it is hoped that the library will continue to grow through the cooperation of universities, government and local government officials.